2019
DOI: 10.3390/data4040137
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases as Markers of Acute Inflammation Process in the Pulmonary Tuberculosis

Abstract: The main factors of pathogenesis in the pulmonary tuberculosis are not only the bacterial virulence and sensitivity of the host immune system to the pathogen, but also the degree of destruction of the lung tissue. Such destruction processes lead to the development of caverns, in most cases requiring surgical interventions besides the drug therapy. Identification of special biochemical markers allowing to assess the necessity of surgery or therapy prolongation remains a challenge. We consider promising markers—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Recently, the contamination and decontamination of inanimate surfaces has been discussed. Inactivation time of the Sars-CoV-2 on surfaces (liquid, solid or gaseous) is still debated [12][13][14][15][16][17][18][19]]. The exposed surfaces to this type of transmission route include:…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the contamination and decontamination of inanimate surfaces has been discussed. Inactivation time of the Sars-CoV-2 on surfaces (liquid, solid or gaseous) is still debated [12][13][14][15][16][17][18][19]]. The exposed surfaces to this type of transmission route include:…”
Section: Introductionmentioning
confidence: 99%
“…TIMPs are very important factors for TB disease, involved in tissue remodeling and repair upon destruction created by MMPs (17,18). Previous studies have identified MMPs as markers of disease severity, bacterial burdens and as a biomarker for disease in PTB and EPTB (17,(19)(20)(21). Relatively, few studies have focused on examining the circulating levels of MMPs and TIMPs as immune biomarkers in both PTB and EPTB.…”
Section: Introductionmentioning
confidence: 99%
“…as a consequence, the concentration of these biomolecules can serve as potential biomarkers [ 13 , 15 ]. Recently, a relatively large dataset of MMPs and TIMP concentrations obtained from patients with the confirmed various drug resistance status of MtB has been published [ 16 ]. This opens up prospects for their evaluation as potential indicators to distinguish between sensitive, MDR, and XDR forms, as well as between healthy and infected persons.…”
Section: Introductionmentioning
confidence: 99%